2011
DOI: 10.1063/1.3596747
|View full text |Cite
|
Sign up to set email alerts
|

Communication: Mode-specific photodissociation of vibrationally excited pyrrole

Abstract: Laser-based spectroscopies coupled with molecular beam techniques facilitated the monitoring of H fragments released in ultraviolet photodissociation of pre-excited isoenergetic vibrational levels of pyrrole. Most noticeably, there was an order of magnitude larger reactivity for an eigenstate primarily consisting of two quanta of ring deformation than for another with one quantum of symmetric C–H stretch. The dynamics, the intramolecular interactions controlling the energy flow, and the mode-selectivity within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 40 publications
(49 reference statements)
0
15
0
Order By: Relevance
“…This anharmonicity was derived from our previously measured photoacoustic Raman spectrum of the fundamental ν 1 stretch, which showed an extremely small feature at 3528.6 cm −1 . 24 Insertion of these bands in the simulated spectra allowed improving the match between them and the corresponding measured PA and action spectra, Fig. 1.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…This anharmonicity was derived from our previously measured photoacoustic Raman spectrum of the fundamental ν 1 stretch, which showed an extremely small feature at 3528.6 cm −1 . 24 Insertion of these bands in the simulated spectra allowed improving the match between them and the corresponding measured PA and action spectra, Fig. 1.…”
Section: Resultsmentioning
confidence: 94%
“…Therefore, it would be of interest to test what is the role played by vibrational energy during pyrrole photoexcitation and particularly to find out how effective is the energy flow out of the initially prepared states. Indeed, our preliminary study 24 showed that excitation of pre-excited pyrrole to the upper potential energy surface and consequently N-H bond cleavage is state dependent. While isoenergetic vibrational eigenstates in the N-H and C-H symmetric stretch fundamentals region were found to lead to quite similar H reactivities, the antisymmetric C-H stretch and even more so the overtone of the ring deformation resulted in enhanced reactivity.…”
Section: Introductionmentioning
confidence: 95%
“…In this section, we apply the GBS algorithm to simulate and optimize the vibrational excitations in pyrrole and butane during vibronic processes mediated by photoexcitation and mechanochemical excitation. In particular, we investigate the effect of vibrational pre-excitation on the photodissociation of the nitrogen-hydrogen (N-H) bond of pyrrole and explain our results with respect to experimental investigations [8,9]. In the case of butane, we explore how the change in the strengths of the external mechanical force can excite vibrational modes that help to dissociate selective carbon-carbon (C-C) bonds and compare the results with those of molecular dynamics simulations and computational analyses [18,40].…”
Section: Applicationsmentioning
confidence: 94%
“…The photochemistry of pyrrole has been the subject of several experimental and theoretical investigations [8,9,[54][55][56]. Pyrrole derivatives are building blocks of important biological molecules, such as chlorophyll and heme [57], and technologically-important systems including solar cells and conducting polymers [58].…”
Section: A Photoexcitation Of Pyrrolementioning
confidence: 99%
See 1 more Smart Citation